Welfare Dynamics in India over a Quarter Century : Poverty, Vulnerability, and Mobility during 1987-2012 - Dang, Hai-Anh H.; Lanjouw, Peter F. (World Bank, Washington, DC, 2020)
This paper analyzes the Indian National Sample Survey data spanning 1987/88-2011/12 to uncover patterns of transition into and out of different classes of the consumption distribution. At the aggregate level, income growth has accelerated, accompanied by accelerating poverty decline. Underlying these trends is a process of mobility, with 40-60 percent of the population transitioning between consumption classes and increasing mobility over time. Yet, the majority of those who escape poverty remain vulnerable. Most of those who are poor were also poor in the preceding period and, thus, are likely to be chronically poor. The characteristics of upwardly mobile households contrast with those of the poor; these households are also far less likely to experience downward mobility. The paper also finds that states exhibit heterogenous mobility patterns.